Controle de Spodoptera frugiperda (J. E. Smith, 1797) em milho Bt com inseticidas aplicados após a irrigação - Bialozor, Adriano (2017)
The corn crop is very important on Brazil’s economy. With two annual corn seasons, Brazil is the third largest grain producer in the world. One of the main corn pests is the fall armyworm, Spodoptera frugiperda, which main feeds on corn leaves. This caterpillar has been a major cause of productivity losses due to insecticide inefficiency, as it is housed inside the leaves whorl, remaining sheltered. On the other hand, the leaflet format of the corn allows the accumulation of water, which can be used to increase the exposure of the caterpillar to the insecticides. This work tested insecticides spray technique after 4mm of foliar irrigation. The research were conducted in the field during 2015/16 and 2016 seasons crops and the objective was to verify the effect of water presence inside the corn leaves whorl in the percentage of attacked plants, damage notes by the Davis scale and the corn yield. The water presence or its absence in the cartridge, two insecticides and five volumes of spray in a three-factorial scheme were used. A control treatment with no insecticide was also conducted. The control of S. frugiperda increase on those treatments with water present inside the leaves whorl, mainly using chlorantraniliprole. The high spray volumes provide a reduction in the damage caused by the fall armyworm. The insecticides chlorantraniliprole and chlorfenapyr provided different protection for corn plants against the fall armyworm damage in both seasons.